2017
DOI: 10.1002/aelm.201600353
|View full text |Cite
|
Sign up to set email alerts
|

First‐Principles Modeling of Point Defects and Complexes in Thin‐Film Solar‐Cell Absorber CuInSe2

Abstract: as the composition of the sample changes from Cu-rich to Cu-poor, so that in the Cupoor samples only one peak is detected. Although only the Cu-poor material is important for actual devices Cu-rich samples give indispensable information for defect identification.First-principles calculations based on the density functional theory (DFT) can be used to obtain important, complementary information about point defects such as formation energies and charge transition levels. [6] A plethora of studies concerning defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 40 publications
2
39
0
Order By: Relevance
“…IV B below). The majority of these defects can be expected to be combined into neutral defect complexes [22][23][24]. The density of remaining single defects is still high enough to cause electrostatic potential fluctuations, since their spatial distribution always shows some statistical fluctuations, causing spatially separated areas with different charges.…”
Section: A Two Acceptors and A Donormentioning
confidence: 99%
See 2 more Smart Citations
“…IV B below). The majority of these defects can be expected to be combined into neutral defect complexes [22][23][24]. The density of remaining single defects is still high enough to cause electrostatic potential fluctuations, since their spatial distribution always shows some statistical fluctuations, causing spatially separated areas with different charges.…”
Section: A Two Acceptors and A Donormentioning
confidence: 99%
“…2. In fact, it has been argued that it is difficult to attribute the third acceptor in CuInSe 2 based on defect calculations [24]. It should be noted that in those CuGaSe 2 films where the third transition is observed as a spatially independent DA3 transition [69,70], it occurs only in very limited and separated spots about 1 μm across.…”
Section: B a Third Shallow Acceptormentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] Increasing the Cu content toward stoi chiometry can considerably reduce the pre sence of such defects and defect complexes. [9][10][11][12] Increasing the Cu content toward stoi chiometry can considerably reduce the pre sence of such defects and defect complexes.…”
mentioning
confidence: 99%
“…
the formation of defect complexes and possibly even phases of ordered defect compounds. [9][10][11][12] Increasing the Cu content toward stoi chiometry can considerably reduce the pre sence of such defects and defect complexes. It has been shown that stoichiometric Cu concentrations can be beneficial for absorber crystallinity, [13] defect density, [7,13] mobility, [14,15] and doping density.
…”
mentioning
confidence: 99%